Extensive Ameloblastoma of the Mandible (TAJ: Journal of Teachers Association, 2009)
The ameloblastoma is the most common and aggressive odontogenic tumour of the jaws. Butonly rarely the anterior portions of the jaws are involved. Since extensive ameloblastoma of themandible crossing the symphysis upto the canine region of the opposite site is a rareoccurrence, so we are encouraged to present this case for academic interest.doi: 10.3329/taj.v15i2.3918TAJ December 2002; Vol.15(2): 93-95